Efficacy, Safety, and Tolerability of a New Low-Dose Copper and Nitinol Intrauterine Device: Phase 2 Data to 36 Months. Issue 4 (April 2020) - Turok, David K.; Nelson, Anita L.; Dart, Clint; Schreiber, Courtney A.; Peters, Kevin; Schreifels, Mary Jo; Katz, Bob
Abstract : OBJECTIVE: To assess in parous and nulliparous women, the efficacy, safety, and tolerability of a new, low-dose copper (175 mm 2 ) intrauterine contraceptive with a flexible nitinol frame provided in a preloaded applicator. METHODS: Institutional review boards at 12 U.S. sites approved this commercially funded project. Patients met standard inclusion and exclusion criteria for a copper-based intrauterine device (IUD), generally consistent with the Centers for Disease Control and Prevention's U.S. Medical Eligibility Criteria for Contraceptive Use, 2016. Intrauterine device placement occurred at any day in the eligible patient's menstrual cycle after assuring she was not pregnant. The primary outcome measure assessed efficacy (measured by the Pearl Index) in this 1-year study with a 2-year extension. Secondary outcomes included placement success, ease of placement, safety as measured by adverse events, and tolerability assessed by discontinuation rate and bleeding and spotting patterns. RESULTS: A total of 286 women provided 5, 640 cycles evaluable for pregnancy. Patients averaged 27.1 years of age. Nulliparous women represented 60.8% of the patients. Over 36 months of observation, we identified two pregnancies (Pearl Index 0.46 [95% CI 0.06–1.67]) and 10 serious adverse events; none were study-related. Successful placement occurred in 283 participants (99.0%). Median (range) continuation times were 2.7 years (0–3.4). We identified five expulsions (1.8%), zero uterine perforations, and one report of pelvic inflammatory disease. Adverse events prompted 30 women (10.6%) to discontinue early in the first year of use with 23 (8.1%) discontinuing for issues of bleeding, pain, or both. Altogether, 107 (37.8%) completed 36 months of device use. Mean bleeding days per cycle decreased from 7.6 in cycle 1 to 5.2 in cycle 13. CONCLUSION: The novel, low-dose copper and nitinol IUD demonstrated high efficacy and safety in this phase 2 U.S. Food and Drug Administration trial and warrants further expanded study in a phase 3 clinical trial. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT02446821. FUNDING SOURCE: Sebela Pharmaceuticals, Inc. Abstract : Continuing to 36 months, the phase 2 study of a low-dose copper intrauterine device with a nitinol frame showed high efficacy and safety.